Performance Evaluation of Thermoelectric Cooling with Two Difference Fluids Medium - Bowo Yuli Prasetyo; Wirenda Sekar Ayu; Fujen Wang (Bandung State Polytechnic (Politeknik Negeri Bandung), 2022)
Thermoelectric has been used in various applications related to cooling systems (TEC). Most researchers focused on expanding the application of TEC and improving heat transfer. The improvement of the heat transfer relied on the configuration, heat exchanger, and fluid medium. However, no previous work has reported the influence of air and water as the fluid’s medium on the TEC performance. Therefore, in this study, the performance of TEC with water and air as working fluids is evaluated experimentally. Besides, several input parameters are controlled to evaluate the TEC performance under different conditions. The results reveal that the variation of working fluid and input parameters influenced the overall TEC output. The increment of TEC cooling capacity is proportional to the input power, mass flow rate, and inlet temperature of the working fluid. While the input power and inlet temperature also vary the heat exchanger thermal resistance. The overall thermal resistance of the water block is averagely ten times lower than that of the heat sink, therefore, the water block is significantly better compared to the heat sink. While the highest COP obtained from the water and air system is 1.72 and 1.41, respectively.